Survival and complications of hybrid prostheses carried out at the Teaching Dental Clinic of the Universidad Peruana Cayetano Heredia between 2013 to 2016. - Araujo Guevara, Karen Gabriela (2022)
Hybrid prostheses in total edentulous patients have improved their quality of life, is essential to know survival and possible complications, to offer reliable treatment. Objectives: to evaluate and record the survival and complications of hybrid prostheses in total edentulous CDD-UPCH patients. Material and methods: descriptive study, observational, retrospective, cross-sectional. Medical records of 37 patients (45 prostheses) installed from 2013 to 2016 were reviewed, data were recorded in Microsoft®Excel2016 and exported to the StataV15 statistical program. A univariate percentage analysis was used for the survival rate and biomechanical complications, and chi2 or Fisher’s exact for the association with variables. Results: Survival (years) was higher: female sex, young patients, installed in upper arches, with early loading and having natural teeth as the antagonist. The most frequent biomechanical complications were: mucositis; being the same in both sexs and arches, with greater results in theolder adult and conventionally loaded prostheses that have mixed prostheses as antagonists; and screw loosening was greater in female patients, older adults with conventionally loaded prostheses and with mixed prostheses as antagonists, without significant differences according to the type of arch.Conclusions: 5-year survival was 84.91% and failure 15.09%. The most frequent biomechanical complications were mucositis and screw loosening, and no associations of survival and biomechanical complications were found with; sex, age group, type of antagonist, compromised arch and type of load.